GAMBARAN MOTIVASI BERPRESTASI SISWA KELAS VIII DI SMP NEGERI 1 BATUJAJAR - Oktoviani, Cinvia; Mustika, Ika; Sekar Ayu Ningrum, Devy (IKIP Siliwangi, 2024)
The purpose of this study was to develop a general description of the achievement motivation of Grade VIII students of SMP Negeri 1 Batujajar, as well as the differences between male and female students. Achievement motivation is a desire within a person that encourages him to strive for a standard or measure of excellence (Mc Clelland, 1987). The subjects of this study were 40 students of class VIII who were selected as research subjects using a purposive sampling technique. This study uses a quantitative method with a quantitative descriptive research design. Data collection was carried out through observation, interviews, questionnaires, or questionnaires, as well as measurement tools based on McClelland's achievement motivation theory (1987). Overall student achievement motivation has an average score of 106 with a percentage of 68%, and there are differences in achievement motivation between male and female students, with male students having an average score of 97 with a percentage of 62% and female students having an average score -an average of 117 with a percentage of 75%.